Treatment of Shiga-Toxin Hus with Severe Neurologic Features with Eculizumab - Jacob H. Umscheid; Collin Nevil; Rhythm Vasudeva; Mohammed Farhan Ali; Nisha Agasthya (Case Reports in Pediatrics)
Hemolytic Uremic Syndrome (HUS) is a constellation of microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. Shiga toxin-producing Escherichia coli- (STEC-) mediated HUS is a common cause of acute renal failure in children and can rarely result in severe neurological complications such as encephalopathy, seizures, cerebrovascular accidents, and coma. Current literature supports use of eculizumab, a monoclonal antibody that blocks complement activation, in atypical HUS (aHUS). However, those with neurologic complications from STEC-HUS have complement activation and deposition of aggregates in microvasculature and may be treated with eculizumab. In this case report, we describe a 3-year-old boy with diarrhea-positive STEC-HUS who developed severe neurologic involvement in addition to acute renal failure requiring renal replacement therapy. He was initiated on eculizumab therapy, with clinical improvement and organ recovery. This case highlights systemic complications of STEC-HUS in a pediatric patient. The current literature is limited but has suggested a role for complement mediation in cases with severe complications. We review the importance of early recognition of complications, use of eculizumab, and current data available.